The impacts of agricultural input subsidies in Malawi - Chibwana, Christopher; Fisher, Monica (International Food Policy Research Institute, 2011)
Achieving food self-sufficiency on a national basis is a high priority for the government of Malawi. The goal of the Farm Input Subsidy Program (FISP) is to enhance food self-sufficiency by increasing smallholder farmers' access to and use of improved agricultural inputs, thereby boosting the incomes of resource-poor farmers. This policy note summarizes the results of recent research by Chibwana, Fisher, Masters, and Shively (CFMS 2010) and by Chibwana, Fisher, and Shively (CFS 2010), on the effectiveness of FISP voucher distribution to smallholder farmers, and on impacts of the FISP on fertilizer use, maize yields, and land allocation. The studies used data from a 2009 survey of 380 farm households in two districts in central and southern Malawi.